PRODUCT CORDIAL LABELING OF DOUBLE PATH UNION OF C3 RELATED GRAPHS - Bapat, Mukund (International Journal of Engineering Technologies and Management Research, 2018)
In this paper we discuss The double path unions obtained on C3 related graphs for product cordial labeling given by Pm(2G’) where G’ = C3, FL(C3), C3+, bull, tail(C3,2P2) etc.